2016
DOI: 10.1002/mus.25069
|View full text |Cite
|
Sign up to set email alerts
|

Perception of pain during electromyography in children: A prospective study

Abstract: When discussing the test with patients, the physician should reassure the patient and parents regarding the degree of pain that may be encountered, which is not materially different from venipuncture. Muscle Nerve 54: 422-426, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 16 publications
(16 reference statements)
2
31
0
Order By: Relevance
“…However, this is very rare if the recording from the second lumbrical muscle is attempted ( Boonyapisit et al, 2001 ). NCS are less uncomfortable than blood sampling for most people ( Alshaikh et al, 2016 ). No one would try to diagnose diabetes without knowing the blood sugar level because blood sampling is painful.…”
Section: Masahiro Sonoo: Review Of Existing Guidelines and Diagnosticmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is very rare if the recording from the second lumbrical muscle is attempted ( Boonyapisit et al, 2001 ). NCS are less uncomfortable than blood sampling for most people ( Alshaikh et al, 2016 ). No one would try to diagnose diabetes without knowing the blood sugar level because blood sampling is painful.…”
Section: Masahiro Sonoo: Review Of Existing Guidelines and Diagnosticmentioning
confidence: 99%
“…EDX are generally well tolerated by most individuals, especially the nerve conduction studies, which are non-invasive. Electromyography is less invasive than phlebotomy ( Alshaikh et al, 2016 ), as the needle gauge is smaller. Needle electromyography is also the only means by which motor axon loss can be definitively established.…”
Section: Daniel Menkes: the Role Of Electrodiagnostic Testing In The mentioning
confidence: 99%
“…The authors concluded that, when discussing the test with patients, it is reasonable to be reassuring with them regarding the level of pain they may experience, and it could be said with confidence that the procedure is not materially different from venipuncture. 1 However, I do not understand why, in their prospective study, they did not use any topical analgesics or local anesthetics before needle insertion, as needle EMG testing can be quite painful, especially for children. Remarkably, they suggested comparing the pain experience with that of venipuncture, yet acknowledged that ".…”
mentioning
confidence: 98%
“…I read with interest the article by Alshaikh and colleagues. 1 In their study they performed a prospective investigation of pediatric patients undergoing nerve conduction studies (NCS) and needle electromyography (EMG). They found that the pain recorded fell within the moderate range on the scoring systems they used, with 66% of the patients describing a level of pain equivalent to or less than that of venipuncture.…”
mentioning
confidence: 99%
See 1 more Smart Citation